2020
DOI: 10.1007/s40123-020-00287-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Emergent Adverse Events in Gene Therapy Trials for Inherited Retinal Diseases: A Narrative Review

Abstract: Patient safety is a primary priority in the conduction of retinal gene therapy trials. An understanding of risk factors and mitigation strategies for post-procedure complications is crucial for the optimization of gene therapy clinical trial protocols. In this review, we synthesize the literature on ocular delivery methods, vector platforms, and treatment-emergent adverse effects in recent gene therapy clinical trials for inherited retinal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 122 publications
0
21
0
Order By: Relevance
“…Indeed, the first approved human AAV gene therapy (Luxturna) is for the treatment of an inherited retinal disease, Leber congenital amaurosis. While systemic delivery of AAV vectors has proved more challenging and recently resulted in the tragic deaths of trial participants ( Wilson and Flotte, 2020 ), their use in the eye has been shown to cause minimal adverse events in clinical trials ( Nuzbrokh et al, 2020 ). While lentiviral vectors can struggle to achieve good transduction efficiency and with transgene expression typically only observed around the site of injection ( Balaggan and Ali, 2012 ; Puppo et al, 2014 ), AAV delivery can achieve transduction patterns exceeding the area of the bleb ( Boye et al, 2016 ; Yiu et al, 2020 ).…”
Section: Cell-specific Targeting In the Degenerate Retinamentioning
confidence: 99%
“…Indeed, the first approved human AAV gene therapy (Luxturna) is for the treatment of an inherited retinal disease, Leber congenital amaurosis. While systemic delivery of AAV vectors has proved more challenging and recently resulted in the tragic deaths of trial participants ( Wilson and Flotte, 2020 ), their use in the eye has been shown to cause minimal adverse events in clinical trials ( Nuzbrokh et al, 2020 ). While lentiviral vectors can struggle to achieve good transduction efficiency and with transgene expression typically only observed around the site of injection ( Balaggan and Ali, 2012 ; Puppo et al, 2014 ), AAV delivery can achieve transduction patterns exceeding the area of the bleb ( Boye et al, 2016 ; Yiu et al, 2020 ).…”
Section: Cell-specific Targeting In the Degenerate Retinamentioning
confidence: 99%
“…Various therapeutic strategies for IRDs are currently under development with an increasing research interest in this field [15,16]. However, any therapy would be promising only when the remaining neural retina is preserved.…”
Section: Introductionmentioning
confidence: 99%
“…Within the field of gene therapy, AAV vectors have been used extensively for therapeutic transgene delivery and in clinical trials for retinal disease they have shown good safety with minimal adverse events [59]. In the case of STGD1 treatments, early attempts involved creation of a single "oversized" transgene containing the complete 6.8 kb ABCA4 coding sequence.…”
Section: Adeno-associated Viral Vectorsmentioning
confidence: 99%